Singing grass, burning sage : discovering Washington's shrub-steppe - Nisbet, Jack, 1949- (Graphic Arts Center Pub., 1999)
This book offers an intriguing introduction to Washington's vast arid lands dominated by fragrant sagebrush, lush coulees, and unique desert creatures and plants.